An integrated personality profiling framework to identify and produce talent in a technical university - Md Saad, Mohd Shamsuri; Yunus, Ahmad Rozelan; Kamarudin, Mohd Fauzi; Ibrahim, Ismail (World Institute for Engineering and Technology Education (WIETE), 2018)
Presented in this article is a proposed holistic and integrated Universiti Teknikal Malaysia Melaka (UTeM) i-PRO personality profiling framework. Dynamic changes in the environment and rapid advancement of technology pose substantial threats to organisations, including higher learning institutions (HLIs), if not carefully managed. One of the strategies to manage this threat is by possessing not only qualified but, more importantly, highly competent talent. Therefore, the ability to identify and develop talent is crucial to assist HLIs, in this case UTeM. It is envisaged that the framework could be developed using qualitative document analyses of major public documents of UTeM and Malaysia National Higher Education Blueprint 2015-2025. As well, various personality principles and instruments would underpin the framework. Subsequently, the proposed framework will be utilised as the basis of a fast-response computer-based personality profiling system that could assists UTeM to identify, develop, and intervene to develop, talent as required by the University.